2021
DOI: 10.3390/nu13051728
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role and Potential of Probiotics in the Field of Mental Health: Major Depressive Disorder

Abstract: The field of probiotic has been exponentially expanding over the recent decades with a more therapeutic-centered research. Probiotics mediated microbiota modulation within the microbiota–gut–brain axis (MGBA) have been proven to be beneficial in various health domains through pre-clinical and clinical studies. In the context of mental health, although probiotic research is still in its infancy stage, the promising role and potential of probiotics in various mental disorders demonstrated via in-vivo and in-vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 155 publications
0
58
0
Order By: Relevance
“…Probiotics are one of the potential adjunctive treatments for psychiatric sequelae among COVID-19 survivors, other than the conventional use of psychotropic medications. Within the last decade, numerous research and clinical trials have been conducted to determine the effects of probiotics on mental health, and clinical trials have proven efficacy for improving mental illness [ 165 ]. A systematic review and meta-analysis have shown that probiotic administration was associated with lower depression and anxiety, relative to the placebo group at the end of treatment [ 166 ].…”
Section: Possible Therapeutic Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotics are one of the potential adjunctive treatments for psychiatric sequelae among COVID-19 survivors, other than the conventional use of psychotropic medications. Within the last decade, numerous research and clinical trials have been conducted to determine the effects of probiotics on mental health, and clinical trials have proven efficacy for improving mental illness [ 165 ]. A systematic review and meta-analysis have shown that probiotic administration was associated with lower depression and anxiety, relative to the placebo group at the end of treatment [ 166 ].…”
Section: Possible Therapeutic Optionsmentioning
confidence: 99%
“…Thus, probiotics come into place in this context, as they have anti-inflammatory, antipathogenic, and antimicrobial properties, which aids the restoration and maintenance of intestinal homeostasis and microbial balance. They mediate its anti-inflammatory effects by modulating pro-inflammatory cytokines, regulating IDO activity, and restoring intestinal barrier function [ 165 ] ( Figure 2 ). A recent meta-analysis revealed that probiotic intervention can significantly reduce the expression of IDO, an important enzyme which metabolizes tryptophan to kynurenine, in the immune cells and plasma of patients across several clinical trials [ 174 ].…”
Section: Possible Therapeutic Optionsmentioning
confidence: 99%
“…Specifically, several known causal pathways exist through which diet can influence brain functioning. For instance, intake of healthy foods is known to decrease inflammation markers and thereby decrease neuroinflammation [ 51 , 52 ]. Similarly, HPA-axis activation is shown to be downregulated through decreased pro-inflammatory cytokines and glucocorticoid levels in response to dietary alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of probiotics include supplements such as yogurt, natto, miso, lactic acid bacteria, and bifidobacteria. They are often used in diseases, such as infectious diarrhea (travelers' diarrhea), antibioticassociated diarrhea, Helicobacter pylori infection, constipation, irritable bowel syndrome, hepatic encephalopathy, Crohn's disease, and ulcerative colitis [86][87][88][89].…”
Section: Probioticsmentioning
confidence: 99%